PKM Usaha Kecil Bandeng Presto di Kelurahan Mlatibaru Kecamatan Semarang Timur Kota Semarang - Widyaswati, Rahmatya; Widiastuti, C. Tri; Meiriyanti, Rita (Jurnal Pengabdian Tri Bhakti, 2020)
The focus of the implementation of this PKM is the development of small-scale presto milkfish businesses in Mlatibaru Village, East Semarang District, Semarang City so that it can grow with improvements in business management. In accordance with the problems faced, the solution given to partners is to improve business management including: 1. Production aspects, 2. financial aspects, 3. Marketing aspects. The solution given is the use of tools with larger capacities, from a financial point of view, the application of simple bookkeeping using the Microsoft Excel application, and from a marketing aspect, the use of online media and attractive packaging. The method in this PKM activity consists of training activities and workshops. The training activities carried out include 1) basic accounting and bookkeeping training 2) bookkeeping training with the Microsoft Excel application 3) Online marketing training. The main activities of this community service include basic financial training and excel bookkeeping, online marketing, product packaging, web creation, addition of appropriate technology to support the production process. MSME players get new insights, know and are motivated to run a business through simple bookkeeping and recording with excel. Business actors also understand that online marketing is currently very important in product marketing, so they inevitably have to keep up with the times if they want their business to grow.